Analisis Yuridis Terhadap Permohonan Perwalian Dalam Pengurusan Izin Jual Tanah Anak Di Bawah Umur - Aris Priyadi (Wijayakusuma Law Review, 2024)
In general, a child is someone who is not yet an adult or is not married. It is not possible for children under this age to carry out legal actions by themselves. For all legal actions, minors are under the authority of the Guardian. To sell land and buildings with the condition that parents act as guardians, you must apply for guardianship and apply for a permit to sell property for minors in the District Court. The purpose of writing this thesis is to understand the application procedures and responsibilities of guardians in processing permits to sell assets of minors in the District Court. This research uses a normative juridical approach, namely, it is carried out by examining theoretical concepts and statutory regulations related to this writing. The data source for this research is a secondary data source, namely data obtained through literature study. The method used in data analysis is a qualitative method, namely interpreted logically and systematically and then conclusions are drawn. The results of this research show that the application submission process consists of: first, the administrative stage, namely: the applicant brings the application letter, submits the case files to the first desk to register the application, pays the down payment, the First Desk Officer submits the SKUM and a copy of the application. Second, the trial stage, namely: The Panel of Judges reads the petition along with the evidence and grants the petitioner's petition. The guardian's responsibility is to make a list of the child's assets under his or her control and record all changes in assets used for the child's benefit until the end of the guardianship period.